Digital Health Assessment Toolkit Guide - World Bank (World Bank, Washington, DC, 2021)
The advancement of technology and the exponential growth of data are providing the opportunity to Low Income Countries and Lower Middle-Income Countries to leapfrog and improve quality of care, decision making, the efficient use of resources, while reducing costs and burden of diseases. Recognizing the promise and potential of digital systems, technologies, and data to support the redesign of PHC and solve pernicious healthcare challenges in countries, digital health assessments intend to be an input and the first step towards the digital journey and to plan and prioritize what a country's health system of the future would look like. As expressed in the WHO’s Global Digital Health Strategy, approved by WHO member states in 2021, ‘Digital health should be an integral part of health priorities and benefit people in a way that is ethical, safe, secure, reliable, equitable and sustainable. It should be developed with principles of transparency, accessibility, scalability, replicability, interoperability, privacy, security and confidentiality.’